(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This research is motivated by the low learning outcomes in Physical Education, Sports, and Health among grade VII students of SMP Negeri 1 Tembilahan Hulu, Indragiri Hilir Regency, where more than 51% of students have not achieved the Minimum Completion Criteria (KKM) of 78. This study employs a quantitative approach with a correlational design to analyze the relationship between physical fitness, infrastructure, and learning motivation in relation to learning outcomes at Penjasorkes. The study population consisted of 382 students, with a sample of 80 students selected using a proportional stratified random sampling technique. Data were collected through TKJI for physical fitness, and Likert scale questionnaires were used for infrastructure and learning motivation. The research instruments were tested for validity and reliability, and then analyzed using multiple linear regression analysis and multiple correlation with the help of SPSS version 25, accompanied by normality and linearity tests as statistical requirements. The results of the Study showed that physical fitness contributed 20%, infrastructure contributed 10.5%, and learning motivation contributed 12.4%, while the simultaneous contribution reached 32.9% to the learning outcomes of Physical Education and Health. This finding confirms that physical fitness factors have the most dominant influence on improving learning outcomes. In conclusion, the correlational approach has proven effective in identifying the influence of physical and psychological variables on student learning outcomes, and it serves as the basis for developing more targeted and data-driven Physical Education and Health learning strategies.